MEN’S LANGUAGE FEATURES USED IN THE NETFLIX SERIES “SEX EDUCATION”: SOCIOLINGUISTICS STUDY - Agustina, Winda; Simatupang, Ervina CM (Jurnal Penelitian Humaniora, 2024)
This research aims to explore the language features employed by male characters in the Netflix series "Sex Education" and to uncover the underlying purposes associated with each linguistic feature utilized by these characters. Adopting a descriptive qualitative approach supported by quantitative data analysis, the study focuses on the verbal expressions of male characters within the series, encompassing words, phrases, clauses, and sentences within dialogues. Through meticulous analysis, the researcher identifies 249 instances of men's language features within the series. These instances were categorized into distinct types, with swear words or taboo language accounting for 30.5%, minimal responses or backchanneling comprising 27.7%, direct questions representing 20.7%, compliments based on skills at 11%, and explicit commands making up 10.1% of the total. The study delves into the various purposes associated with men's language features. These purposes encompass expressions of masculinity, establishment of dominance, facilitation of rapport, concealment of vulnerability, and negotiation of social hierarchies within diverse cultural contexts. In contrast, women's language features typically serve to express uncertainty, convey emotions, elicit responses, soften utterances, and emphasize points. The distinctiveness of men's language features lies in their inclination towards asserting dominance, taking specific actions, offering compliments, and gathering specific details, reflecting the multifaceted nature of gendered communication dynamics within the series.